Deglaciation and ice shelf development at the northeast margin of the Laurentide Ice Sheet during the Younger Dryas chronozone - Furze, Mark F. A.; ńkowski, Anna J.; McNeely, Morgan A.; Bennett, Robbie; Cage, Alix G. (Boreas, 2017)
Core 2011804-0010 from easternmost Lancaster Sound provides important insights into deglacial timing and style at the marine margin of the NE Laurentide Ice Sheet (LIS). Spanning 13.2–11.0 cal. ka BP and investigated for ice-rafted debris (IRD), foraminifera, biogenic silica and total organic carbon, the stratigraphy comprises a lithofacies progression from proximal grounding line and sub-ice shelf environments to open glaciomarine deposition; a sequence similar to deposits from Antarctic ice shelves. These results are the first marine evidence of a former ice shelf in the eastern Northwest Passage and are consistent with a preceding phase of ice streaming in eastern Lancaster Sound. Initial glacial float-off and retreat occurred >13.2 cal. ka BP, followed by formation of an extensive deglacial ice shelf during the Younger Dryas, which acted to stabilize the retreating margin of the NE LIS until 12.5 cal. ka BP. IRD analyses of sub-ice shelf facies indicate initial high input from source areas on northern Baffin Island delivered to Lancaster Sound by a tributary ice stream in Admiralty Inlet. After ice shelf break-up, Bylot Island became the dominant source area. Foraminifera are dominated by characteristic ice-proximal glaciomarine benthics (Cassidulina reniforme, Elphidium excavatum f. clavata), complemented by advected Atlantic water (Cassidulina neoteretis, Neogloboquadrina pachyderma) and enhanced current indicators (Lobatula lobatula). The biostratigraphy further supports the ice shelf model, with advection of sparse faunas beneath the ice shelf, followed by increased productivity under open water glaciomarine conditions. The absence of Holocene sediments in the core suggests that the uppermost deposits were removed, most likely due to mass transport resulting from the site's proximity to modern tidewater glacier margins. Collectively, this study presents important new constraints on the deglacial behaviour of the NE Laurentide Ice Sheet, with implications for past ice sheet stability, ice-rafted sediment delivery, and ice−ocean interactions in this complex archipelago setting.